2022
DOI: 10.24251/hicss.2022.883
|View full text |Cite
|
Sign up to set email alerts
|

Using Objectives and Key Results (OKRs) and Slack: A Case Study of Coordination in Large-Scale Distributed Agile

Abstract: Today, many large-scale software projects have members working from home, which has changed the way teams coordinate work. To better understand coordination in this setting, we conducted a case study through which we examined two teams in a large-scale agile project by observing meetings and conducting 17 interviews. Through the lens of Relational Coordination Theory (RCT), we analyzed the use of the goal-setting framework Objectives and Key Results (OKRs) and the collaboration tool Slack. Slack was used for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…The team members could thus anticipate one another's needs, and adjust their co-location plans accordingly. Our work builds on the findings that Slack is an essential tool for coordination in distributed teams [20]. Further, in our teams, the shared Slack etiquette created a common understanding of the availability of team members, by for example agreeing on traditions such as sending "good morning" messages when ready for work, and changing Slack icons when unavailable.…”
Section: Discussionmentioning
confidence: 81%
“…The team members could thus anticipate one another's needs, and adjust their co-location plans accordingly. Our work builds on the findings that Slack is an essential tool for coordination in distributed teams [20]. Further, in our teams, the shared Slack etiquette created a common understanding of the availability of team members, by for example agreeing on traditions such as sending "good morning" messages when ready for work, and changing Slack icons when unavailable.…”
Section: Discussionmentioning
confidence: 81%
“…Also, most teams used two communication platforms (the most popular were Discord, Facebook Messenger, Microsoft Teams, and Slack). Slack has been identified as a significant tool that offers various advantages such as facilitating improved communication by reducing the barrier to seeking assistance and encouraging greater participation through the visibility of queries and topics under discussion [34,38]. In student teams, Ross [34] found that Slack seems to improve the quality of group communications and perceived learning outcomes from group work.…”
Section: Discussionmentioning
confidence: 99%
“…Av den grunn er det også forsket mye på koordinering i utviklingssettinger i stor skala, både i norske og internasjonale fag miljøer (Dingsøyr et al, 2018;Edison et al, 2022;Palopak et al, 2023). Fra denne forskningen har vi fått beskrivelser av en rekke ulike koordineringsmekanismer, som smidige møter (Moe et al, 2018), roller (Bass & Haxby, 2019) og ulike verktøy og prosesser (Stray et al, 2022). Derimot har vi mang let en systematisk tilnaerming til å analysere og forstå slike mekanismer som er spesifikk for storskala utviklingssettinger, ettersom det meste av eksisterende forskning bruker teorier fra andre fagfelt og empiriske settinger (Palopak et al, 2023).…”
Section: Koordinering I Storskala Smidig Utviklingunclassified